Development of Pd-coated ceramic electrodes in hybrid sulphur cycle. (16th March 2009) - Kawamura, Hirotaka; Mori, Masashi; Hashimoto, Shin-ichi; Uotani, Masaki
The Hybrid Sulphur (HyS) cycle has attracted much attention as a mass production process for hydrogen. It consists of an electrolysis step and a thermal decomposition one. In order to achieve high efficiency for hydrogen production and operational cost reduction, some developments in electrode materials with high corrosion resistance, high electrical conductivity and low anodic potential is a key issue for the electrolysis in H2SO4 solution.Our research group pointed out that some electronic conductive ceramics, which are titanium (Ti)-based pyrochlores (chemical formula: A3+2Ti4+2O7) and perovskites (chemical formula: A2+Ti4+O3), might be some of the candidates for anode base materials. We developed the sintering process of electronic conductive ceramics which had high corrosion resistance and high electrical conductivity. In this paper, our research activities for the development of a new type of anode material are introduced, i.e., the material development of electronic conductive ceramics, corrosion resistance evaluation and electrical conductivity evaluation of Ti-based ceramics in a 50 weight(wt.)% H2SO4 solution at the operating temperature are summarised. Additionally, the application of a palladium (Pd)-coating technique on the titanate was evaluated using the electroless deposition technique, in order to provide some catalytic properties to the materials.